Correlation Study of Carbon Monoxide (CO) Air Exposure Level with Blood COHb Level of Basement Officer in Surabaya Mall - Safiatur Nur Rohmah (JURNAL KESEHATAN LINGKUNGAN, 2019)
Gas CO is formed as a result of incomplete combustion. The material containing carbon monoxide is gas emission from motorcycle vehicle which is toxic to humans. This study aims to analyze the correlation between CO gas that also known as Carbon monoxide gas in the air with COHb level of blood parking basement officers in Surabaya "x" mall. This study was analytical observational with cross sectional design and the data was analyzed by Chi-Square test. The number of samples used was 15 parking basement officers and a control group of 15 people as a comparison. The results of measurement of CO gas levels in 3 parking points were more than standards recommendation. While the other 3 points in the control area were below the quality standard. All of samples in the parking basement officers had COHb levels >5% and for control areas there were 11 persons who had COHb levels of <5% and 4 people who had COHb levels of >5%. The results suggested that there was a significant correlation between the characteristics of individuals with COHb levels, such as duration of work (p = 0.040), nutritional status (p = 0.047) and smoking habits (p = 0.046). While variable of age (p = 0.070) and personal protective equipment (PPE) use (p = 0.128) showed no significant correlation. In addition, there was a significant correlation between exposure of CO gas and blood COHb levels in basement car park officers in Surabaya "X” Mall (p = 0.000), and there was a distinction between COHb level of blood basement car park officers in the "x" mall building and the control group with a value of p = 0.000. Based on the results, it is suggested for car park officers to cease smoking, go to places with more oxygen, maintain diet and do exercise regularly. It is also suggested and recommended for agencies is to put more attention regarding exhaust fans' maintenance and sufficiency.